Placebo-Controlled Trial of Tofacitinib Monotherapy in Rheumatoid Arthritis - Fleischmann, Roy; Kremer, Joel; Cush, John; Schulze-Koops, Hendrik; Connell, Carol A; Bradley, John D; Gruben, David; Wallenstein, Gene V; Zwillich, Samuel H; Kanik, Keith S (The New England journal of medicine, 2012)
In a placebo-controlled trial, monotherapy with tofacitinib, an oral Janus kinase inhibitor, reduced the symptoms and signs of rheumatoid arthritis. Adverse events associated with tofacitinib included infections, decreased neutrophil counts, and elevated LDL cholesterol levels. Rheumatoid arthritis is a chronic autoimmune disease that is characterized by inflammation and destruction of joints. The disease has a major effect on health status and quality of life and imposes a substantial economic burden on patients and society. 1 Tofacitinib (CP-690,550) is a novel oral Janus kinase (JAK) inhibitor that is being investigated as a targeted immunomodulator and disease-modifying therapy for rheumatoid arthritis. Tofacitinib preferentially inhibits signaling through heterodimeric receptors associated with JAK3, JAK1, or both, with functional selectivity over JAK2-paired receptors. 2 Inhibition of JAK1 and JAK3 by tofacitinib blocks signaling for several cytokines (interleukins 2, 4, 7, 9, 15, . . .